Investigating the spatial pattern of older drivers' eye fixation behaviour and associations with their visual capacity - Sun, Qian (Chayn); Xia, Jianhong (Cecilia); Falkmer, Torbjörn; Lee, Hoe (2016)
Visual capacity generally declines as people age, yet its impact on the visual search patterns along sections of different road during actual driving still remains undocumented. This on-road driving study simultaneously recorded 30 older drivers' eye movement and precise vehicle movement trajectories. The vehicle positions were linked to every identified eye fixation for each individual driver, so that the locations of the driver's gaze origin in geo-spatial coordinates were obtained. Spatial distribution pattern of drivers' eye fixations were then mapped and analysed. In addition, the associations between older drivers' visual ca-pacity (processing speed, divided and selective attention) and their eye fixation patterns in various driving manoeuvres were investigated. The results indicate that driving scenarios have a significant impact on older drivers' visual patterns. Older drivers performed more frequent eye fixations at roundabouts, while they tended to fixate on certain objects for longer periods during straight road driving. The key findings show that the processing speed and divided attention of older drivers were associated with their eye fixations at complex right-turns; drivers with a lower capacity in selective attention performed less frequent eye fixations at roundabouts. This study has also demonstrated that visualisation and spatial sta-tistics are effective and intuitive approaches to eye movement analysis.